Estimation of the detected background by the future gamma ray transient mission CAMELOT. Issue 7 (10th October 2019) - Řípa, Jakub; Galgóczi, Gábor; Werner, Norbert; Pál, András; Ohno, Masanori; Mészáros, László; Mizuno, Tsunefumi; Tarcai, Norbert; Torigoe, Kento; Uchida, Nagomi; Fukazawa, Yasushi; Takahashi, Hiromitsu; et al.
Abstract: This study presents a background estimation for the CubeSats Applied for MEasuring and LOcalising Transients (CAMELOT), which is a proposed fleet of nanosatellites for the all‐sky monitoring and timing‐based localization of gamma ray transients with precise localization capability at low Earth orbits. CAMELOT will allow us to observe and precisely localize short gamma ray bursts (GRBs) associated with kilonovae, long GRBs associated with core‐collapse massive stars, magnetar outbursts, terrestrial gamma ray flashes, and gamma ray counterparts to gravitational wave sources. A fleet of at least nine 3U CubeSats is proposed to be equipped with large and thin CsI(Tl) scintillators read out by multipixel photon counters (MPPC). A careful study of the radiation environment in space is necessary to optimize the detector casing, estimate the duty cycle due to the crossing of the South Atlantic Anomaly and polar regions, and minimize the effect of the radiation damage of MPPCs.